Bioadsorptive Removal of the Pollutant Zn(II) from Wastewater by Delftia tsuruhatensis Biomass - Samiah Hamad Al-Mijalli (Applied and Environmental Soil Science)
This investigation suggests the applicability of Delftia tsuruhatensis biomass for the removal of Zn(II) from the aqueous environment. Twenty-three zinc-resistant bacterial strains were isolated from contaminated rhizosphere soils. Selectively, the bacterium strain SA-101 was selected as the most zinc-resistant and identified by 16S rRNA sequencing as Delftia tsuruhatensis SA-101. D. tsuruhatensis SA-101 has been assigned the accession number MW629784 in the GenBank database. The optimal pH and reaction contact time for Zn(II) removal by D. tsuruhatensis SA-101 were 6.0 and 30 min, respectively. Moreover, the equilibrium and kinetic models have been applied to the Zn(II) biosorption process. The Zn(II) concentration was estimated using atomic absorption spectroscopy. The qmax for bioadsorptive Zn(II) removal was calculated to be 90.91 ± 0.36 mg/g. The biosorption equilibrium was well fitted with the Freundlich model and the pseudo-second-order kinetic model. So, using the biomass of D. tsuruhatensis SA-101 as a biosorbent of Zn(II) from industrial wastewater represents a promising and viable alternative to chemical treatment from an environmental and economic view.